Specialized microbiome of the cave-dwelling sponge Plakina kanaky (Porifera, Homoscleromorpha). Issue 4 (16th March 2020) - Ruiz, César; Villegas-Plazas, Marcela; Thomas, Olivier P; Junca, Howard; Pérez, Thierry
ABSTRACT: The recent description of the polychromatic sponge Plakina kanaky revealed original microsymbionts, with some morphotypes recorded for the first time in Homoscleromorpha and others never before observed in other sponge groups. Illumina 16S amplicon sequencing was used to characterize this microbial community by comparing contents of seven specimens of this Plakinidae with five other sponge species: one Homoscleromopha of the Oscarellidae family and four Demospongiae. A total of 256 458 sequences of the hypervariable V5-V6 region of the 16S rRNA gene were clustered into 2, 829 OTUs at 97% similarity, with Proteobacteria, Poribacteria and Chloroflexi being the most abundant phyla. The Plakina kanaky specific community appeared to be mainly composed by five OTUs representing about 10% of the total microbiome. Among these, the filamentous bacterium Candidatus Entotheonella, which was among the dominant morphotypes previously observed in the mesohyl and the larvae of P. kanaky, was detected in all studied specimens. However, other original and dominant morphotypes could not be assigned to a known prokaryotic taxon. This cave dwelling sponge species harbors a distinctive microbiome composition of potential taxonomic and metabolic novelties that may be linked to its ecological success in such extreme environments. Abstract : Original sponge microbiome that can explain their ecological success in submarine caves.